TELAAH KOMPARATIF BISNIS MULTI LEVEL MARKETING KONVENSIONAL DAN MULTI LEVEL MARKETING SYARIAH - Nurjannah; Mukhtar Lutfi; Nasrullah Bin Sapa; Muhammad Afief Mubayyin; Herianti (Universitas Islam Negeri Mataram, 2022)
Multi-Level Marketing Business is a business method that is growing rapidly in today's society. However, regarding the permissibility of this business, there are still different understandings between the parties. Likewise regarding the difference between conventional MLM and Islamic MLM. This article aims to examine more deeply the differences between Sharia MLM and Conventional MLM and explore contemporary fiqh views regarding this business. The method used is descriptive qualitative using secondary data obtained from literature related to the discussion.Multi Level Marketing is also commonly known as sales intermediary services. This service (broker) in fiqh terminology called samsarah/simsar is a trade intermediary (people who sell goods and find buyers) or intermediaries between sellers and buyers to facilitate buying and selling. Samsarah/simsar activities in the form of distributors, agents or members, in fiqh include ijarah contracts, namely a transaction using the services of another person in return, incentives or bonuses (ujrah), all scholars consider it permissible (mubah). MLM Business Regulations in the realm of sharia are contained in the DSN-MUI Fatwa Number: 75/DSN-MUI/VII/2009 concerning Guidelines for Sharia Tiered Direct Selling. Sharia MLM and Conventional MLM are almost the same, but there are differences in terms of regulation, organization and business objectives, one of which is sharia MLM operating in sharia,